2010
DOI: 10.2174/1874836801004010121
|View full text |Cite
|
Sign up to set email alerts
|

Failure Mode and Drift Control of MRF-CBF Dual Systems

Abstract: Abstract:In this paper, a new method for designing moment resisting frame (MRF) -concentrically braced frame (CBF) dual systems failing in global mode is presented. Starting from the analyses of the typical collapse mechanisms of such structural typology subjected to seismic horizontal forces, the method is based on the application of the kinematic theorem of plastic collapse. Beam and diagonal sections are assumed to be known quantities, because they are designed to resist vertical loads and horizontal forces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…More recently, Tenchini et al [2] confirmed this result highlighting the limited benefit in using HS steel for seismic application in moment resisting frames (MRFs) compared to using solely MC steel, because the design of MRFs is conditioned by the need to guarantee lateral stability and to satisfy the performance limits in terms of story displacements. On the contrary, when the seismic design is associated to Theory of Plastic Mechanism Control (TPMC) [3][4][5][6][7][8][9][10][11][12][13][14][15], the HS steel has provided adequate seismic performance where it is possible to see a reduction of the steel weight compared to frames in complacent with European code. In fact, in order to ensure a collapse mechanism of global type, this approach provides a plastic http://dx.doi.org/10.1016/j.engstruct.2016.06.001 0141-0296/Ó 2016 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Tenchini et al [2] confirmed this result highlighting the limited benefit in using HS steel for seismic application in moment resisting frames (MRFs) compared to using solely MC steel, because the design of MRFs is conditioned by the need to guarantee lateral stability and to satisfy the performance limits in terms of story displacements. On the contrary, when the seismic design is associated to Theory of Plastic Mechanism Control (TPMC) [3][4][5][6][7][8][9][10][11][12][13][14][15], the HS steel has provided adequate seismic performance where it is possible to see a reduction of the steel weight compared to frames in complacent with European code. In fact, in order to ensure a collapse mechanism of global type, this approach provides a plastic http://dx.doi.org/10.1016/j.engstruct.2016.06.001 0141-0296/Ó 2016 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the actual behavior is elasto-plastic so that structures exhibit significant lateral displacements before failure, and second order effects cannot be neglected in the design procedure. To this scope, a linearised mechanism equilibrium curve can be used to represent the structural behavior [1,7]:…”
Section: Proposed Design Proceduresmentioning
confidence: 99%
“…By properly solving the 3n s design conditions provided by Eq. (9) [1,7], the sum of column plastic moments, reduced due to the contemporary action of axial forces, required to prevent the development of undesired collapse mechanisms is obtained for each storey. The final step consists in distributing such sum among the storey columns.…”
Section: Proposed Design Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it consists on the extension of the kinematic theorem of plastic collapse to the concept of mechanism equilibrium curve. This design approach was successively extended to a large variety of structural typologies [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. In 2015 TPMC was developed also with reference to the reinforced concrete frames [38][39][40].…”
Section: Introductionmentioning
confidence: 99%